From Fivefold to Five-in-One Ministry: Mega-Ecclesiological Leadership (Dis)Continuities in Southern Africa - Tagwirei, Kimion (Religions, 2024)
In Southern Africa in recent years, the governance and ecclesiologies of mega-Pentecostal churches have been drifting away from upholding collective and complementary fivefold ministries to individualistic and selfish five-in-one ministries. Studies indicate that a fivefold ministry advances inclusive ecclesiological leadership, edification, and transformational integral mission. At present, mega and related forms of emerging neo-Pentecostalism have developed exclusive, prophetic, apostolic, and executive ecclesial leadership, which are characterized mainly by authoritarian governance, celebrity leadership, leader-centered ecclesiology, and congregational manipulation and exploitation. Such church governance and ecclesiologies enable leaders to indoctrinate their subordinates and congregants to submit to and depend on them for everything. The effect is that followers are rendered dormant, under what this submission describes as five-in-one ministry, which leaves one person claiming to possess all ministerial gifts and leadership capabilities and relegating everyone else to being idle followers. Although much has been published about African Pentecostal leadership and ecclesiologies, studies on African megachurch governance, leadership styles and ministries are few. Through a literature review and participant observation, this paper uncovers and troubleshoots the effects of five-in-one megachurch governance and ecclesiologies in Africa. It discerns and addresses drivers of the five-in-one ministry and makes recommendations, such as reforming megachurch governance, leadership styles, and ecclesiologies; integrating ecumenism with leadership development; and developing inclusive economic sustainability.